LAW ENFORCEMENT AGAINST DESTRUCTIVE FISHING IN INDONESIA: JUDICIAL REASONING AND ECOLOGICAL JUSTICE IN JUDGMENT No. 152/Pid.Sus-LH/2025/PN.Pya - Dedi Afrizal Hidayat; Rina Rohayu Harun; Yulias Erwin; Nurjannah Septyanun (Universitas Labuhanbatu, 2026)
Destructive fishing continues to pose a serious threat to Indonesia's marine ecosystems, yet judicial responses remain predominantly oriented toward criminal punishment rather than ecological restoration. This article examines how destructive fishing regulations are implemented through judicial reasoning and whether court decisions incorporate ecological justice as part of environmental law enforcement. This study employs a normative legal research method using statutory, conceptual, and case approaches to analyze Judgment No. 152/Pid.Sus-LH/2025/PN.Pya together with relevant fisheries and environmental legislation. The findings demonstrate that the judgment primarily reflects a conventional retributive model of criminal law enforcement by emphasizing imprisonment, fines, and the confiscation or destruction of evidence, while restorative obligations such as ecosystem rehabilitation, environmental recovery, and compensation for ecological damage are absent from the judicial order. These findings indicate that the implementation of destructive fishing regulations in judicial practice remains focused on formal legal compliance and deterrence rather than substantive ecological justice. This study contributes by proposing a responsive ecological law enforcement model that integrates criminal sanctions with ecosystem restoration, thereby encouraging courts to institutionalize environmental recovery as an essential component of judicial outcomes in destructive fishing cases.Keywords: destructive fishing; ecological justice; environmental restoration; law enforcement; responsive law.